2023
DOI: 10.1111/cas.15891
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and nongenetic mechanisms for colorectal cancer evolution

Abstract: The stepwise accumulation of key driver mutations is responsible for the development and malignant progression of colorectal cancer in primary sites. Genetic mouse model studies have revealed combinations of driver gene mutations that induce phenotypic changes in tumors toward malignancy. However, cancer evolution is regulated by not only genetic alterations but also nongenetic mechanisms. For example, certain populations of metastatic cancer cells show a loss of malignant characteristics even after the accumu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…MSI, on the other hand, is characterized by a high frequency of mutations in short repetitive DNA sequences, primarily due to defects in the DNA mismatch repair system. MSI-high tumors are more responsive to immunotherapies due to their increased mutational load. , …”
Section: Molecular Profiling Of Colorectal Cancermentioning
confidence: 99%
“…MSI, on the other hand, is characterized by a high frequency of mutations in short repetitive DNA sequences, primarily due to defects in the DNA mismatch repair system. MSI-high tumors are more responsive to immunotherapies due to their increased mutational load. , …”
Section: Molecular Profiling Of Colorectal Cancermentioning
confidence: 99%
“…The APC gene holds substantial importance as a frequently mutated tumor suppressor gene within CRC. 10 Situated on chromosome 5q21-q22, this gene spans 8535 nucleotides and comprises 21 exons encoding a 310 kDa protein containing 2843 amino acids. A pivotal site for both germline and somatic mutations of APC lies within exon 15, encompassing 75% of the gene's coding sequence.…”
Section: Apc Mutations In Crcmentioning
confidence: 99%
“…18, 19 Evidently, APC intricately interacts with critical signaling pathways and biological processes implicated in CRC development. 10 Recent investigations have shown that restoring APC functionality can promote tumor regression and restore crypt homeostasis in CRC, suggesting that the Wnt pathway is a promising therapeutic target for CRC treatment. 20…”
Section: Apc Mutations In Crcmentioning
confidence: 99%